DAMPAK KONTEN MARKETING, SOSIAL MEDIA MARKETING DAN KENYAMANAN ONLINE TERHADAP KEPUTUSAN PEMBELIAN PADA MARKET PLACE AESTHETE.YOURLIFE DI KOTA BATAM - rainbow; Wasiman (SCIENTIA JOURNAL, 2025)
This research aims to explore the impact of content marketing, social media marketing, and online convenience on consumer purchasing decisions online through marketplaces. The development of information technology has transformed consumer shopping habits, making factors such as content marketing, social media marketing, and online convenience crucial in influencing purchasing decisions. Content marketing focuses on providing relevant and valuable information to attract and retain audiences, while social media marketing utilizes platforms like Facebook and Instagram to build more personal interactions with consumers. Online convenience includes aspects such as easy navigation, data security, and fast transaction processes. This research uses primary data from consumer surveys and secondary data from relevant literature. The research findings are expected to provide insights for business practitioners in developing effective digital marketing strategies and help academics gain a deeper understanding of factors influencing consumer behavior in the digital era. Thus, this research aims to contribute to facing the increasingly tight competition in the online market.